Early Childhood Empowerment In Improving Clean and Healthy Living Behaviors in The Raudahatul Athfal, Sukabumi - Erna Safariyah; Mustopa Saepul Alamsyah; Anggun Fajar Ramadhani; Kartika Tarwati; Siti Um Um Andriyani (Dinasti International Journal of Education Management And Social Science, 2025)
Clean and Healthy Living Behavior (PHBS) encompasses health-related practices driven by personal awareness, enabling families and their members to independently manage their health and actively participate in community activities. Cultivating healthy habits from an early age is crucial, particularly during the preschool years (ages 3-6), a period marked by rapid growth and a natural inclination to explore. Proper nutritional intake and overall health are essential to support this growth. Among the factors influencing early childhood health, clean and healthy living behaviors play a significant role. This community service initiative focuses on instilling these habits in children at Raudhatul Athfal (RA) schools, chosen due to the prevalence of diseases stemming from limited knowledge about PHBS. The program includes interactive health education activities, such as engaging games like the Puzzle of Cita-citaku, Healthy Food Dice, and Clap Your Hands. Running from November 2023 to April 2024, the program has achieved notable results, with 80% of participants demonstrating the ability to simulate proper handwashing techniques, identify healthy food options, dispose of garbage appropriately, and maintain personal hygiene. This initiative not only enhances children's awareness and habits but also supports broader objectives, such as promoting student engagement beyond the campus and applying lecturers’ expertise to benefit the community. The collaborative effort underscores the importance of integrating education and practical activities to foster a healthier, more informed generation.